The Efficacy of Bevacizumab, Sorafenib, and Retinoic Acid on Rat Endometriosis Model - Ozer, Hatice; Boztosun, Abdullah; Acmaz, Gokhan; Atilgan, Remzi; Akkar, Ozlem Bozoklu; Kosar, Mehmet Ilkay (Sage Publications Inc, 2013)
Blood vessels are necessary for development and maintenance of the endometriosis and blood flow supplies oxygen and essential nutrient to the disease. Local angiogenesis is regulated by vascular endothelial growth factor (VEGF) and inhibitors of VEGF may be a novel therapeutic approach. We inducted endometriosis in 43 rats and they were randomly allocated into 4 groups. The rats in group I (control n = 11) were given no medication. The rats in group II (n = 11) were given bevacizumab. The rats in group III (n = 11) were given Sorafenib, and the rats in group IV (n = 10) were given retinoic acid (RA). Then groups were compared for microvessel density, VEGF, soluble tyrosine-kinase receptor, ovarian reserve, and treatment effectivity. All these medications were effective on endometriosis and we detected that volume of endometriotic implants were significantly decreased. Ovarian reserve was not affected from the medication, in addition RA have induced reproductive capacity.
Keywords: endometriosis; rat; treatment